Analisis Tekstual Puisi Cinta Itu, Kamu karya Moammar Emka - Normasunah Normasunah (STKIP Paris Barantai, 2021)
This research descriptive qualitative method. Data collection carried by library techniques, data collection based on written sources and note-taking techniques, keeping records of relevant data according the goals and objectives of study. data source the book Cinta Itu, Kamu, by Moammar Emka. The results of the analysis can be concluded that the poetry in the book Cinta Itu, Kamu (1) Grammatical means consist: Reference which is divided into three, namely persona reference, demonstrative reference and comparative reference. Substitution is indicated by replacement of certain lingual units other lingual units. ellipsis is characterized the omitted element, but mentioned earlier. Conjunctions divided into coordinative conjunctions, subordinative conjunctions, conjunctions between sentences, correlative conjunctions. (2) The lexical facilities consist: Repetition divided into three types, namely: full repetition, repetition changes in shape, and partial repetition. Synonym which characterized by existence of word equation between free morpheme and bound morpheme, word for word, word with phrase or vice versa. Antonyms characterized the presence of absolute antonyms and hierarchical antonyms. Collocation is indicated by the presence of words that tend to be used simultaneously. Hyponym is characterized by words that are represented by hypernimes which become superordinate from the mention of other words. Keywords: Textual analysis, poetry